Case report: Amisulpride therapy induced reversible elevation of creatine kinase-MB and bradycardia in schizophrenia - Hu, Ze-Rui; Yang, Zhen-Zhen; Wang, Xu-Bo; Chu, Hong-Shuo; Liu, Chuan-Xin (Frontiers in Psychiatry, 2022)
Introduction: Schizophrenia is regarded as one of the most severe, disabling, and costly mental illnesses. Hence, early effective prevention and treatment are critical to the prognosis of patients. Amisulpride, a first-line atypical antipsychotic medication that acts as a blocker of the D2 and D3 dopamine receptors, is used in varying doses for the treatment of both positive and negative symptoms of schizophrenia. Reversible amisulpride-induced elevation of the myocardial enzyme spectrum with bradycardia is a rare condition. Case presentation: We report a 26-year-old patient diagnosed with first-episode schizophrenia. This patient was treated with amisulpride (400mg/d), but no clinical benefits were obtained. Meanwhile, amisulpride caused elevation of the myocardial enzyme spectrum with asymptomatic bradycardia. After stopping the medication, these parameters normalised. Conclusion: We described a rare side reaction of amisulpride. Psychiatrists should take this side effect seriously in the clinical setting. The mechanism of this adverse reaction warrants further investigation and debate. When this side effect occurs during treatment, reducing the dosage of amisulpride and subsequently discontinuing medication, along with monitoring the electrocardiogram and serum myocardial enzymes, may be the most appropriate treatment protocol.